How advertising avoidance affects visual attention and memory of advertisements - Onișor, Lucian-Florin; Ioniță, Daniela (Journal of Business Economics and Management, 2021)
Understanding how to more effectively advertise is an important area for practitioners, many of whom are struggling to stay in business. Nowadays, both product and corporate branding are important and given the increase in online advertising, additional research to better understand advertising avoidance is needed. Most advertising avoidance studies to date measure either task attention or attention to advertising. This paper contributes to a more holistic view of attention by examining two distinct online tasks, such as reading information and buying products, and two forms of advertising, such as product brand advertisements and corporate brand advertisements. An eye-tracking experiment with 121 respondents show that when reading, users look more at advertisements that increase the memory of the ads. Regardless of the task performed, the corporate brand ads are more memorable than the product brand ads even if the product ads attract more attention. The longer the user stays on a website, the more the user will look at the ads and the easier it will be to remember them. However, ads are considered to be distractors for online users, therefore, to increase their effectiveness they must be more engaging and provide value for the audience.